IMPLEMENTATION OF DESIGN THINKING METHODS IN UI/UX DESIGNING JOB SEARCHING APPLICATIONS - Sriardi, Mohammad Didit; -, Tukino; Nurapriani, Fitria (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
Major changes in the job search have occurred with the development of the digital age. Therefore, user experience enhancement (UserExperience, UX) and user interface (UserInterface, UI) in job search applications is becoming an urgent need. This study aims to explore the application of the methoddesign thinkingin designing the UI/UX of a job search application namedCareer Hunt.Design thinking, a user-centric approach, enabling developers to understand deeply the needs, challenges and expectations of users, and create innovative and effective solutions. There are five stages used in this study: empathy, definition, ideation,prototype, and testing / test. In this study, interviews and contextual observations were conducted to gain a deeper understanding of user behavior and needs. Based on these findings, the main issues need to be solved, and then facilitate the sessionbrainstormingto generate a variety of potential solutions. Then, developprototypebased on those ideas and do user testing.feedbackreceived is used for literacy and further improvement. As a result, useDesign Thinkingin designUI/UXThis job search application has succeeded in increasing user satisfaction levels as well as job search efficiency. Keywords:Job Search,Career Hunt, Design Thinking, UI/UX